PENGARUH TEKANAN ANISOTROPIK PADA BINTANG NEUTRON - A. M. Setiawan; A. Sulaksono (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
We investigate the anisotropic factor Ïƒ of neutron stars based on the Doneva-Yazadjiev (DY), Herrera-Barreto (HB), and Bowers-Liang (BL) anisotropic models. We assume that the neutron stars matter consist of nucleons, leptons, and hyperons. We obtain that the corresponding models predict neutron stars maximum mass consistent with PSR J1614-2230 and PSR J0348+0432. Keywords: Hyperon, Neutron Stars, and Anisotropic Pressure.